Unveiling the molecular arsenal: genome sequencing and in silico secretome analysis of Fusarium verticillioides provide insights into maize root rot pathogenesis - Narváez-Zapata, José Alberto; Alaníz-Cuevas, Yadira; Chávez-Medina, J. Alicia; Espinoza-Mancillas, Mariela Guadalupe; Maldonado-Mendoza, Ignacio E.; Singh, Rupesh Kumar; Quiroz-Figueroa, Francisco Roberto (Frontiers in Plant Science, 2025)
IntroductionFusarium verticillioides (Fv) is a major phytopathogen responsible for maize root rot, affecting crop productivity globally. A probable infection mechanism has been suggested in Fusarium, involving the disruption, and partial degradation of the plant cell wall by the colonizing fungal hyphae.MethodsIn this study, the highly virulent Fv DA42 strain was subjected to whole-genome sequencing, in silico secretome analysis and SEM structural analysis to elucidate its pathogenic mechanism.ResultsThe assembled genome comprised 175 contigs (=200 pb) totaling 42.27 Mb, with an N50 of 1.24 Mb and GC content of 48.51%. A total of 14,198 protein-coding genes were predicted, of which 997 (7.03%) correspond to classical secreted proteins. The predicted secretome includes 262 carbohydrate-active enzymes (CAZymes), 62 proteases, 400 effectors, 481 virulence factors and 288 uncharacterized proteins. Functional annotation revealed enrichment in enzymatic activities such as pectinesterases, feruloyl esterases, and glucosidases, highlighting their role in host cell wall degradation. Chromosomal distribution showed secretome genes concentrated on chromosomes 4 and 8, with the highest density (49.2 genes/Mb) on chromosome 10. Scanning electron microscopy confirmed degradation of maize root hairs and epidermis seven days post-infection, this degradation may have occurred days prior to the observation. STRING analysis identified key proteins like FVEG_10795 (pectinesterase) and FVEG_09361 (feruloyl esterase) as central to coordinated enzymatic attacks.DiscussionThis integrative analysis offers crucial insights into Fv pathogenicity and provides a molecular basis for targeted antifungal strategies and resistance breeding in maize.